Good-Bye Hegemony! : Power and Influence in the Global System - Simon Reich, Richard Ned Lebow (Princeton University Press, 2014)
American leaders had contradictory goals in the decades following World War II. They wanted to foster democracy and economic development, but were opposed to left-wing parties and governments. They wanted the order they associated with hierarchy and to preserve the United States’ extraordinary position in 1945 as far and away the world’s most powerful country. Policy makers sometimes made trade-offs among these goals, as they did by consistently supporting right-wing dictatorships over their democratic opponents in the name of anticommunism. More often than not they denied trade-offs, convincing themselves they could pursue all these goals simultaneously. American academics catered to this illusion by developing the concept of hegemony. It made it appear that hierarchy in the form of American hegemony was beneficial to democracy and development and was welcomed by major actors everywhere outside the Soviet bloc. Americans considered Moscow’s opposition to US hegemony as opposition to global order and thus a sign of aggressive intentions. A growing bloc of neutrals who also expressed their disquiet, with India as its most vocal spokesmen, were dismissed as misguided, or even as dupes of Moscow. Instead of speaking truth to power, international relations scholars, with few notable exceptions, became spokesmen, therapists, and propagandists on behalf of the burgeoning national security establishment for the assumptions that undergirded American foreign policy. Almost seventy years later, American realists and liberals continue to defend hegemony in theory and practice. They ignore the evidence that hegemony was only partial and short-lived and that American efforts to maintain order (e.g., in Vietnam, Afghanistan, and Iraq) were a primary source of disorder in the international system. Despite ample evidence to the contrary, they delude themselves into believing that most of the world welcomes American leadership and that its policies invariably engender stability.